Hybrid Solenoids Based on Magnetic Shape Memory Alloys - Manuel Mauch; Marco Hutter; Bernd Gundelsweiler (Actuators, 2023)
The mobility of today and tomorrow is characterized by technological change and new challenges in drive concepts such as electric or hydrogen vehicles. Abolishing conventional combustion engines creates even more need for switching or valve technology in mobility systems. For switching and controlling purposes, solenoids are used in large numbers and in a wide variety of applications, thus making a significant contribution to the overall success of the energy transition, and not only in the automotive sector. Despite their long existence, continued research is being carried out on solenoids involving new materials and actuator concepts. Great interest is focused on providing an adjustable force–displacement characteristic while simultaneously reducing the noise during switching. At IKFF, research is being conducted on hybrid electromagnets in the border area of switching and holding solenoids. This paper aims to present the major advantages of this hybrid drive concept based on an electromagnetic FEA simulation study of two drive concepts and specially developed and characterized prototypes with magnetic shape memory (MSM) alloys. The concepts differ in the spatial orientation of the MSM sticks to generate an active stroke of the plunger, which contributes to a beneficial force–displacement characteristic and lower power consumption while minimizing switching noise.